2012
DOI: 10.1183/09031936.00017712
|View full text |Cite
|
Sign up to set email alerts
|

Aclidinium inhibits cigarette smoke-induced lung fibroblast-to-myofibroblast transition

Abstract: Cigarette smoking contributes to lung remodelling in chronic obstructive pulmonary disease (COPD). As part of this remodelling, peribronchiolar fibrosis is observed in the small airways of COPD patients and contributes to airway obstruction. Fibroblast-to-myofibroblast transition is a key step in peribronchiolar fibrosis formation.This in vitro study examined the effect of cigarette smoke on bronchial fibroblast-tomyofibroblast transition, and whether aclidinium bromide inhibits this process. Human bronchial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…The activated fibroblasts contribute to the deposition of collagen and other ECM components [21, 22], which increase the thickness of small airways and contribute to airflow limitation, leading to pulmonary fibrosis and airway remodeling. CS is a key risk factor in COPD and has been reported to promote the transition of fibroblasts to myofibroblasts [4]. In the present study, we observed by immunohistochemistry and western blotting that COPD rats displayed high expression of α -SMA, which is a hallmark of myofibroblasts, in lung tissues, whereas the variations could be attenuated by ginsenoside Rg1 treatment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The activated fibroblasts contribute to the deposition of collagen and other ECM components [21, 22], which increase the thickness of small airways and contribute to airflow limitation, leading to pulmonary fibrosis and airway remodeling. CS is a key risk factor in COPD and has been reported to promote the transition of fibroblasts to myofibroblasts [4]. In the present study, we observed by immunohistochemistry and western blotting that COPD rats displayed high expression of α -SMA, which is a hallmark of myofibroblasts, in lung tissues, whereas the variations could be attenuated by ginsenoside Rg1 treatment.…”
Section: Discussionsupporting
confidence: 53%
“…In response to inflammatory stimulation, the persistent activated pulmonary fibroblasts/myofibroblasts secrete various cytokines and growth factors, leading to a protease/antiprotease imbalance and abnormal production of extracellular matrix (ECM). Cigarette smoke (CS) is a major risk factor for the development of COPD [3] and has been shown to cause chronic airway inflammation and induce lung fibroblast-to-myofibroblast transition [4, 5]. Thus, inhibiting the activation of pulmonary fibroblasts could be an attractive therapeutic target in treating small airway fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tiotropium and 4-DAMP have been shown to inhibit alveolar macrophage mediated migration of neutrophils from patients with COPD patients [27]. Moreover, tiotropium inhibited TGF-b-induced matrix metalloproteinase-1 (MMP-1) and MMP-2 expression in human lung fibroblasts [57], and aclidinium has been shown to inhibit TGF-b and cigarette smoke-induced fibroblast to myofibroblast differentiation [37,58]. These studies indicate that non-neuronal acetylcholine might contribute to airway inflammation and remodeling of airway cells in an autocrine or paracrine manner.…”
Section: Bronchoconstriction As a Driver Of Airway Remodelingmentioning
confidence: 98%
“…This takes place under chronic inflammatory conditions. Recently it has been shown that the remodelling into myofibroblasts could be reversed by administration of the anticholinergic aclidinium bromide, by silencing M1, M2 or M3 mAChR mRNA or by degradation of ACh using AChE treatment [47]. Thus, the NNCS is involved in one of the key steps of COPD and asthma consolidation.…”
Section: Respiratory Systemmentioning
confidence: 99%